Analisis Pengaruh Kinerja Keuangan, Firm Size Dan Cash Flow Terhadap Return Saham Perusahaan Manufaktur Di Indonesia - Farah Margaretha Leon; Ricky (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2017)
The purpose of this study is to analyze how much influence financial ratios, firm size, cash flow from operations to EPS on companies listed in Indonesia Stock Exchange. Analysis of the data used in this study is to test the t test and the partial F test for simultaneous testing. Results of this study concluded that the data meets the classical assumptions. Partially, regression analysis showed that NPM, ROE, total assets, and firm size has a positive and significant impact on EPS. However, current ratio, debt to equity ratio, price -book value, and the variable cash flow from operations does not affect EPS. Results of this study can be used by investors as one of the basic decision to invest in the stock market, and the company can provide information that investors are interested to invest their capital.